Initial Experience With the Absorb Bioresorbable Vascular Scaffold Below the Knee: Six-Month Clinical and Imaging Outcomes. (April 2015) - Varcoe, Ramon L.; Schouten, Olaf; Thomas, Shannon D.; Lennox, Andrew F.
Purpose: To investigate a new bioresorbable vascular scaffold for the treatment of focal tibial and distal popliteal lesions.Methods: Tibial and distal popliteal angioplasty was performed in 15 limbs of 14 patients (9 men; median age 82 years) with critical limb ischemia (CLI, n=7) or severe claudication. The 18 lesions (mean length 22.2±14.0 mm) were implanted with 22 everolimus-eluting bioresorbable scaffolds (Absorb). Clinical and ultrasound follow-up was performed at 1, 3, 6, and 12 months to detect restenosis and evaluate safety, midterm restenosis rate, and clinical improvement.Results: Immediate technical success was 100%, although a single limb suffered 2 scaffold thromboses on the first day; it was salvaged with repeat endovascular intervention. All patients were available for surveillance examinations during a follow-up of 6.1±3.9 months; no patient died. Of the 15 limbs in the analysis, clinical improvement was present in 12 (4 of 7 CLI patients); there was no amputation, bypass surgery, or evidence of binary restenosis on follow-up sonographic examination.Conclusion: Midterm follow-up for this small pilot sample demonstrates acceptable safety and patency results, together with freedom from all major adverse limb events, using the Absorb bioresorbable vascular scaffold below the knee.